TEKNOLOGI PENGOLAHAN LIMBAH BIJI KARET MENJADI PRODUK OLAHAN MAKANAN RINGAN - Riabarleany, Dhena; Heriyanto, Heri; Muliyadini, Winny (Jurnal Pengabdian Dinamika, 2017)
Lebak is a district in Banten province with high potential in agriculture and plantation. Rubber seed is produced from rubber plantation which was not well utilized. Rubber seed can be processed to be some food products, such as bread, chip, and traditional snack called opak. This program purposed to give the information to the society especially lived in Lebak district about food processing from rubber seed. Method used in this program was held by the socialization in front of Lebak district society in the form of discussion and practices. This program results food product ( bread, chip, and opak) from rubber seed.